MIĘDZY STYLISTYKĄ A STATYSTYKĄ W TEŚCIE KULTURY INFORMATYCZNEJ - Ubermanowicz, Stanisław (Wydawnictwo Naukowe UAM w Poznaniu, 1996)
At the beginning of the era of global multimedia in addition to developing computer literacy it is necessary to take first steps in creating a new computer awareness. It can be assumed that attitudes toward computers are cognitive representations of temporary states of this awareness and their fluctuations are practical indicators of the quality of computer literacy courses. The authors discuss various aspects of the process of constructing a standardized questionnaire to measure students' computer awareness. The results of empirical verification on technologically as well as culturally diverse populations constitute the basis for refining the questionnaire.
Keywords: kultura informatyczna; alfabetyzacja medialna; świadomość informatyczna; informatyka; efektywność; informatics culture; computer literacy; computer awareness; informatics; effectiveness